Impact of Professional Development Training Curriculum on Practicing Algebra Teachers - Naseer, Mariyam Shahuneeza (International Journal on Emerging Mathematics Education, 2018)
Algebra is a foundation for mathematics reasoning and complex problem-solving which then requires mathematics teachers to have adequate proficiency to make their students understand about it. The mathematics teachers in the Maldives, however, lacked both the algebraic content and pedagogical knowledge. This study aims to present a mathematics professional development training curriculum designed to address the issue of the teachersâ performance in algebra. There were five participants involved in this study who teach mathematics in the sixth grade of elementary school. Desimoneâs conceptual model for professional development was used to guide the mathematics professional development for algebra teachers discussed in this paper. This mathematics professional development was found to improve the algebraic content and pedagogical knowledge of the participants, which in turn improved student performance.